الآثار القانونية لتعاطي المنشطات في الألعاب الرياضية طبقا لمقاصد الشريعة الإسلامية : دراسة تحليلية مقارنة - دفراوي، أحمد سعد أحمد (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2021)
The taking of performance-enhancing drugs, such as anabolic-androgenic steroids, cell and gene therapy technologies, and similar other prohibited substances, among athletes has been increasing. The abuse of these substances violates the rules of ethics, laws, and objective of Shariꜥah (Maqasid of Shariꜥah) since such will have a considerable effect on the level and purity of sports achievement. Consequently, these prohibited acts are deemed as cheating and deception and are impinging on athletes' right to life as well as their right to physical integrity. Due to the consequences, Shariꜥah prohibits taking and giving of physical steroids because the nature and illegal effects of such activities contradict the five fundamental objectives of Shariꜥah (Maqasids). Moreover, statutory laws, such as the Olympic Charter and the World Anti-Doping Code of disciplinary direction, have been developed to fight such illegal actions and incidents since their inception. On this basis, this study seeks to address the problem of the absence of a proper criminal law on the cases and incidents of taking and giving physical steroids associated with pathological symptoms or purely criminal consequences. To achieve this objective, the researcher has employed descriptive, analytical, and comparative methods to analyse relevant data for this study. The results obtained propose that every single act of taking physical steroids and other similar substances in sports games, which violates sports laws or affect athletes' right to life – bodily integrity, is followed by the revival of disciplinary and penal legal effects in response as represented by the legal responsibility system. Hence, it recommended that there exists a necessity to conclude an international treaty that will help identify those involved in illegal cases of taking or giving physical steroids (athletes and their supporting teams), which are associated with criminal effects for the purpose of questioning them about their criminal activities. Preferably, all Muslim countries should be parties to this treaty in order to save the nation's true wealth as represented by teenagers and young people.